Level of Knowledge and Attitude towards COVID-19 among High School students in Depok - Arnold Arnold; Vycke Yunivita Dewi; Fifi Veronica (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Depok is the city with the largest COVID-19 cases in West Java, Indonesia. The application of health protocol for high school student as the second-largest age group,’s depends on the level of knowledge and attitudes that can be affected by gender. This study aimed to determine the level of knowledge and attitudes based on the gender of high school students towards COVID-19 in Depok.Methods: This study was a cross-sectional analytic study, conducted from June 2020 to June 2021. The data was collected using a Google form application with a validated questionnaire and the research subjects were high school students in Depok. Knowledge of COVID-19 was assessed with 18 questions, true or false questions. Correct answer was assigned 1 point. Points were summed for a total knowledge score of Poor, Moderate, or Good. Attitude was assessed with 6 questions. For each answer given, subjects with a total score of >18 were assessed as a positive attitude.Results: Of a total of 273 respondents, 238 had met the inclusion criteria. Most of the respondents had a moderate level of knowledge (60.5%) and most of the respondents (89%) had a positive attitude towards COVID-19. No significant differences in level of knowledge or attitude between males and females (p>0.05).Conclusions: High school students in Depok have a moderate level of knowledge and have a positive attitude in dealing with COVID-19 which is not influenced by gender. The lack of information regarding the timing of vaccine administration and examination of COVID-19 needs to be a concern for high school students in Depok.